Meningkatkan Hasil Belajar Pai Melalui Model Pembelajaran Teams Games Tournament (TGT) Pada Siswa Kelas XI Di SMA Ar-Risalah Kota Lubuklinggau - Hasani, Muhammad; Helandri, Joni; Yunus, Muhammad (Edification Journal : Pendidikan Agama Islam, 2023)
The right learning model will be able to improve student learning outcomes. Based on the results of the reflection in the pre-cycle, several problems were found in the learning process, namely the teacher used an inappropriate model and did not use learning media. This has an impact on low learning outcomes in Islamic Religious Education and Budi Pekerti lessons, marked by 67% of students who do not reach the KKM. Based on these problems, researchers made efforts to improve PAI learning outcomes for 30 students in class XI SMA Ar-Risalah for the 2022/2023 academic year by applying the Team Game Tournament (TGT) model. This research is Classroom Action Research (CAR), researchers act as educators and subject educators as observers. Learning is carried out in 2 cycles with 3 meetings. Based on the results of the analysis of the study, it can be seen that with the application of the TGT model, student learning outcomes have increased from 33% in the pre-cycle, 57% in the first cycle and in the second cycle, reaching 97% of the students' completeness. This increase is an implication of increasing student learning activities.